Development of Spherical Actuator with L-Shaped Yoke - Yu-Wen Huang; Hao-Wen Chung; Yu-Ming Chen; Chien-Sheng Liu; Ming-Fu Chen (Actuators)
In this paper, a two-DOF L-shaped yoke spherical actuator based on the principle of traditional voice coil actuators is developed. By utilizing the shape characteristics of the yoke and the magnetization direction of the magnet, the magnetic flux is concentrated and the magnet is shared, thereby improving the performance of the actuator. In the design process, SOLIDWORKS 2018 software is used for design modeling and assembly simulation, ANSYS Maxwell 2018 software is employed for magnetic circuit analysis and electromagnetic simulation, while MATLAB is utilized for analyzing the dynamic characteristics through a mathematical model. A prototype was also fabricated, and torque measurement experiments were conducted to verify the performance and feasibility of the proposed design.